2005
DOI: 10.1194/jlr.m400424-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase 1: a target of 9-hydroxystearic acid in the inhibition of cell growth in human colon cancer

Abstract: Recent studies have shown that an endogenous lipoperoxidation product, 9-hydroxystearic acid (9-HSA), acts in colon carcinoma cells (HT29) as a growth inhibitor by inducing p21 WAF1 in an immediate-early, p53-independent manner and that p21 WAF1 is required for 9-HSA-mediated growth arrest in HT29 cells. It is conceivable, therefore, to hypothesize that the cytostatic effect induced by this agent is at least partially associated with a molecular mechanism that involves histone deacetylase 1 (HDAC1) inhibition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 22 publications
4
54
1
Order By: Relevance
“…There are three general classes of HDACs: class I HDACs, which are strictly nuclear, class II HDACs, which shuttle between the nucleus and cytoplasm, and class III HDACs, which require NADþ [23]. The class I HDACs 1, 2, and 3 have been reported to be upregulated in cancer cells from different tissue origins [24][25][26][27][28][29][30][31][32]. A recent metaanalysis of a variety of human cancers indicated that HDAC3 may be one of the most frequently upregulated genes in cancer cells [33].…”
Section: Introductionmentioning
confidence: 99%
“…There are three general classes of HDACs: class I HDACs, which are strictly nuclear, class II HDACs, which shuttle between the nucleus and cytoplasm, and class III HDACs, which require NADþ [23]. The class I HDACs 1, 2, and 3 have been reported to be upregulated in cancer cells from different tissue origins [24][25][26][27][28][29][30][31][32]. A recent metaanalysis of a variety of human cancers indicated that HDAC3 may be one of the most frequently upregulated genes in cancer cells [33].…”
Section: Introductionmentioning
confidence: 99%
“…9 -HSA supplemented in micro-molar amounts to the human colon cancer cell line HT29 was previously shown to result in a strong inhibition of cell proliferation as well as cellular differentiation toward benign phenotype (Calonghi et al , 2005). To evaluate the effect of 9 -HSA on the proliferation of RPCs during retinogenesis and later on the stem cell niche of the retina, we assessed the proliferative state of retinae from embryos injected with 9 -HSA.…”
Section: Resultsmentioning
confidence: 99%
“…We previously demonstrated that tumor growth inhibitory effect of 9 -HSA on human colon carcinoma cells (HT29) in vitro was mediated through a direct fatty acid interaction, leading to a decrease of the enzymatic activity of the histone deacetylase 1 (HDAC1) (Calonghi et al , 2005; Parolin et al , 2012). In zebrafish HDAC1 was shown to be required for aspects of the eye and central nervous system development, and for the establishment of neural crest cell populations (Cunliffe, 2004; Cunliffe & Casaccia-Bonnefil, 2006; Harrison et al , 2011; Ignatius et al , 2013; Stadler et al , 2005; Yamaguchi, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HDAC1 target genes include Bax, p21 WAF1/CIP1 , p27 KIP1 , and cytokeratin 18 (CK18) (Zhou et al, 2000; Lagger et al, 2002; Bandyopadhyay et al, 2004). While others have shown that HDAC1 may be inhibited by synthetic compounds [e.g., SAHA (Richon et al, 1998) and M344 (Kim et al, 2003)] or metabolic by‐products [e.g., 9‐HSA (Calonghi et al, 2005)] that have similar structures as the HDAC reaction transition‐state intermediate, it is reasonable to speculate that HDAC1 needs to be tightly regulated by a proactive mechanism in a cell type‐specific manner. To our knowledge, maspin is the first endogenous polypeptide inhibitor of HDAC1 identified.…”
Section: The Novel Co‐factors and Targets Of Maspinmentioning
confidence: 99%